The written world : the power of stories to shape people, history, civilization - Puchner, Martin. 1969- (New York : Random House, 2017)
"The story of literature in sixteen acts, from Alexander the Great and the Iliad to ebooks and Harry Potter, this engaging book brings together remarkable people and surprising events to show how writing shaped cultures, religions, and the history of the world"--
"Great stories of people, history, and literature are combined to show how the power of the written word has influenced civilizations throughout time. Puchner writes about Ezra and the Old Testament, a young woman in 9th century Japan who wrote the first novel, a wild story about Cervantes and pirates, how Benjamin Franklin became the father of print in the United States, and more. Over this remarkable, engaging book, Puchner tells stories of creative people whose lives and beliefs led them to create groundbreaking foundational texts, and how those texts affected the world they were born into. Puchner offers a truly comprehensive and worldwide literary perspective, spanning time and cultures, from the first written story--The Epic of Gilgamesh--to the wordsmiths of Mande in Africa, to Harry Potter. He also focuses on writing technologies, including the invention of paper, the printing press, and the modern book, and how they shaped not just writing, but religion and economy, too. Taking us from clay tablets and ancient scrolls, all the way to internet tablets and scrolling down on computers today, Puchner will change the way you view the past, present, and future of literature. Readers will find new discoveries about old texts they love, and new stories they hadn't known before, as Martin Puchner tells the story of literature in 17 acts: how stories shaped history, and gave us THE WRITTEN WORLD"--
Includes bibliographical references (pages 341-392) and index.
English.
Keywords: Literature and society; Literature -- History and criticism; Books and reading